How much of the diversification discount can be explained by poor corporate governance? - Hoechle, Daniel; Schmid, Markus; Walter, Ingo; Yermack, David (Journal of Financial Economics, 2012)
We investigate whether the diversification discount occurs partly as an artifact of poor corporate governance. In panel data models, we find that the discount narrows by 16% to 21% when we add governance variables as regression controls. We also estimate Heckman selection models that account for the endogeneity of diversification and dynamic panel generalized method of moments models that account for the endogeneity of both diversification and governance. We find that the diversification discount persists even with these controls for endogeneity. However, in selection models the discount disappears entirely when we introduce governance variables in the second stage, and in dynamic panel GMM models the discount narrows by 37% when we include governance variables.